Application of phased antenna array with digital beamforming to establish the internal radio network of the distributed satellite - Ilchenko, M.; Narytnyk, T.; Prisyazhny, V.; Kapshtyk, S.; Denisenko, M.; Narushkevich, A. (ХНУРЕ, 2023)
The possibility of application of the Phased Antenna Array with Digital Beamforming (PAA-DB) to establish the Internal Radio Network (IRN) of the Distributed Satellite (DS) is shown, which allows increasing the efficiency of the IRN by using the spatial separation of information flows between Core and Edge Satellites. The issues considered are related to choosing the Reference Coordinate System in which it is proposed to measure the relative motion of the satellite of the DS. An Orbital Coordinate System of the Core Satellite is proposed as the Reference Coordinate System. It is shown how the information about the coordinates of the Edge Satellites in the Orbital Coordinate System of the Core Satellite enables to obtain information about the coordinates of the Edge Satellites in the Orbital Coordinate System by the method of recalculation.